Whole metagenome sequencing of chlorinated drinking water distribution systems. Issue 12 (17th October 2018) - Douterelo, Isabel; Calero-Preciado, Carolina; Soria-Carrasco, Victor; Boxall, Joby B.
Abstract : This research highlights the potential of whole metagenome sequencing to help protect drinking water quality and safety. Abstract : There has been an explosion of research into the microorganisms present within drinking water distribution systems (DWDS). However, previous studies have focused mainly on the taxonomic composition and little is known about the actual genes composing the metagenomes of DWDS and their function or whether such information could be used for genetic profiling and monitoring processes taking place in DWDS. We use here for the first time whole metagenome shotgun sequencing to characterise microbial communities from both biofilm and bulk water samples from operational, chlorinated DWDS. Gene content analysis revealed habitat-specific (biofilm vs. water) differences in terms of organisms as well as gene functions, suggesting adaptation to specific environments. In addition, several resistance mechanisms were identified preferentially within biofilms, including genes associated with the prevention and repair of disinfectant radical-induced damage and antibiotic resistance. This research highlights the potential of such information to help protect drinking water quality and safety in the future following further research and wider application.